Analisis Keterpaduan Struktur Kurikulum Matematika dalam Mewujudkan Pembelajaran Matematika yang Efektif - Henra Putra Nainggolan; Sri Ulfah Afriani Dalimunthe; Mariam Nasution (Yayasan Darussalam Bengkulu, 2026)
The mathematics curriculum plays a crucial role in achieving effective learning through the integration of objectives, content, process, and assessment. However, in practice, there are still inconsistencies between curriculum components, which leads to mathematics learning being procedurally and outcome-oriented. This study aims to analyze the integration of the mathematics curriculum structure in achieving effective mathematics learning. The study used a qualitative approach with library research methods through a review of scientific journals, books, education policy documents, and previous research relevant to the 2020–2025 period. Data analysis techniques were carried out through systematic data reduction, categorization, interpretation, and synthesis. The results of the study indicate that the effectiveness of mathematics learning is greatly influenced by the alignment of learning objectives, systematic and contextual content organization, a student-centered learning process, and assessments that comprehensively measure mathematical thinking skills. Thus, the integration of objectives, content, process, and assessment is a primary prerequisite for creating mathematics learning that is effective, meaningful, and aligned with the demands of 21st-century competencies.